翻訳と辞書
Words near each other
・ "O" Is for Outlaw
・ "O"-Jung.Ban.Hap.
・ "Ode-to-Napoleon" hexachord
・ "Oh Yeah!" Live
・ "Our Contemporary" regional art exhibition (Leningrad, 1975)
・ "P" Is for Peril
・ "Pimpernel" Smith
・ "Polish death camp" controversy
・ "Pro knigi" ("About books")
・ "Prosopa" Greek Television Awards
・ "Pussy Cats" Starring the Walkmen
・ "Q" Is for Quarry
・ "R" Is for Ricochet
・ "R" The King (2016 film)
・ "Rags" Ragland
・ ! (album)
・ ! (disambiguation)
・ !!
・ !!!
・ !!! (album)
・ !!Destroy-Oh-Boy!!
・ !Action Pact!
・ !Arriba! La Pachanga
・ !Hero
・ !Hero (album)
・ !Kung language
・ !Oka Tokat
・ !PAUS3
・ !T.O.O.H.!
・ !Women Art Revolution


Dictionary Lists
翻訳と辞書 辞書検索 [ 開発暫定版 ]
スポンサード リンク

negation normal form : ウィキペディア英語版
negation normal form

In mathematical logic, a formula is in negation normal form if the negation operator (\lnot, ) is only applied to variables and the only other allowed Boolean operators are conjunction (\land, ) and disjunction (\lor, ).
Negation normal form is not a canonical form: for example, a \land (b\lor \lnot c) and (a \land b) \lor (a \land \lnot c) are equivalent, and are both in negation normal form.
In classical logic and many modal logics, every formula can be brought into this form by replacing implications and equivalences by their definitions, using De Morgan's laws to push negation inwards, and eliminating double negations. This process can be represented using the following rewrite rules:
:\lnot (\forall x. G) \to \exists x. \lnot G
:\lnot (\exists x. G) \to \forall x. \lnot G
:\lnot \lnot G \to G
:\lnot (G_1 \land G_2) \to (\lnot G_1) \lor (\lnot G_2)
:\lnot (G_1 \lor G_2) \to (\lnot G_1) \land (\lnot G_2)
A formula in negation normal form can be put into the stronger conjunctive normal form or disjunctive normal form by applying distributivity.
==Examples and counterexamples==
The following formulae are all in negation normal form:
:(A \vee B) \wedge C
:(A \wedge (\lnot B \vee C) \wedge \lnot C) \vee D
:A \vee \lnot B
:A \wedge \lnot B
The first example is also in conjunctive normal form and the last two are in both conjunctive normal form and disjunctive normal form, but the second example is in neither.
The following formulae are not in negation normal form:
:A \Rightarrow B
:\lnot (A \vee B)
:\lnot (A \wedge B)
:\lnot (A \vee \lnot C)
They are however respectively equivalent to the following formulae in negation normal form:
:\lnot A \vee B
:\lnot A \wedge \lnot B
:\lnot A \vee \lnot B
:\lnot A \wedge C

抄文引用元・出典: フリー百科事典『 ウィキペディア(Wikipedia)
ウィキペディアで「negation normal form」の詳細全文を読む



スポンサード リンク
翻訳と辞書 : 翻訳のためのインターネットリソース

Copyright(C) kotoba.ne.jp 1997-2016. All Rights Reserved.